Remnants of the Portuguese-era fort on Kaka Baptista garden - Mumbai Archive Project Team (Jio Institute, 2024)
Remnants of the Portuguese-era fort which stood on top of Mazagon Hill. The hill overlooked Mazagon harbour and the fort protected the harbour from piracy. The British destroyed the fort in 1881, and built an underground water reservoir on the hill. It was originally named after John Hay Grant, the Municipal Commissioner of Bombay from 1871 to 1881. Later it was renamed after Joseph ‘Kaka’ Baptista, a leading figure of the East Indian community.